1995
DOI: 10.1177/002199839502901602
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Analysis and Resulting Design Recommendations for Unidirectional and Multidirectional End-Notched Flexure Tests

Abstract: Results are presented from a theoretical investigation of the effects of stacking sequence on the energy release rate in laminated composite end-notched flexure test specimens. Deflections and energy release rates of unidirectional and multidirectional ENF specimens are obtained by classical laminated plate theory, shear deformable plate theory, and three dimensional finite element analyses. It is shown that the distribution of energy release rate varies across the front of an initially straight delamination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…Similar results were also obtained in a related investigation, in which mixed-mode energy release rates were computed for an ENF specimen with the same layup and interface location as the SLB specimen [80,82]. This study indicated that the computed energy release rates, G II and G III , did not exhibit a significant variation when ∆a/h was kept within the suggested range.…”
Section: Application Examplessupporting
confidence: 85%
“…Similar results were also obtained in a related investigation, in which mixed-mode energy release rates were computed for an ENF specimen with the same layup and interface location as the SLB specimen [80,82]. This study indicated that the computed energy release rates, G II and G III , did not exhibit a significant variation when ∆a/h was kept within the suggested range.…”
Section: Application Examplessupporting
confidence: 85%
“…In order to reduce the inevitable thermally induced residual contractions that occur during cooling after consolidation, coupling stiffness B ij of the chosen laminates is desired to be zero or very close to zero (Daniel andIshai, 1994 or Jones, 1975). The specimen stacking sequence is also chosen to minimize and keep the non-dimensional ratio of the specimens flexural rigidities, D c ; ðD c ¼ D 2 12 =D 11 D 22 Þ smaller than 0.25 in each delamination arm in order to minimize non-uniform toughness value distribution and the errors in the perceived values of critical fracture toughness (Davidson et al, 1995). To obtain a defined delamination according to the standard test method for mixed mode delamination (ASTM D6671, 2002) a 50 mm wide polyimide film (Kapton Ò ) is placed in the mid-plane of each lay-up as a delamination starter.…”
Section: Test Specimensmentioning
confidence: 99%
“…For example, anticlastic deformations resulting from bending-bending couplings may generate highly curved delamination fronts and a considerable mode III component at the specimen edges [7,12]. Davidson et al [12] suggested a 0.25 upper bound for the parameter D c ¼ ðD 12 Þ 2 =ðD 11 D 22 Þ, where D ij represent the Classical Lamination Theory bending stiffness coefficients of each specimen arm. On the other hand, bending-twisting and membrane-bending couplings are generally present in 0=h and h/Àh specimens.…”
Section: Selection Of Specimen Stacking Sequencesmentioning
confidence: 99%
“…a 1 ¼ À0:1 Â 10 À6 =°C and a 2 ¼ 26 Â 10 À6 =°C, and the temperature variation was 100°C. In the next paragraphs, we present the results for 0/0, 0/45, 0/90 and 45/ )45 specimens, since they represent the limit cases of elastic couplings [12]. Fig.…”
Section: Selection Of Specimen Stacking Sequencesmentioning
confidence: 99%